P282 Bacterial co-infections in Mucormycosis infected COVID-19 patients: experience from a tertiary care center in India. (20th September 2022) - Sharad, Neha; Srivastava, Smriti; Ningombam, Aparna; Kiro, Vandana; Varma, Sharin; Srivastav, Sharad; Malhotra, Rajesh; Mathur, Purva
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM: During the second wave of COVID-19 in India, there was a deluge in Mucormycosis cases; which posed a serious threat as both conditions require extended hospital stay thus serving as an ideal setting for secondary infections. Objectives: 1. To ascertain the prevalence and anti-microbial profile of hospital-acquired secondary infections in COVID- 19 patients with Mucormycosis. 2. To evaluate the outcome in these patients and compare it with the outcome of COVID-19 patients with Mucormycosis but without any other secondary infection. Methods: A 2-month retrospective observational study was conducted, where we compared outcomes in two groups of COVID-19 patients with Mucormycosis, one group being patients with secondary infections and the other group including patients without secondary infections. A total of 180 samples from suspected cases of Mucormycosis, that underwent evaluation by conventional methods, KOH mount and cultures on SDA, were included. Fungal pathogens were identified from the positive cultures, based on macroscopic and microscopic features, as per standard Mycological methods. Secondary infections inpatients were studied based on conventional bacteriological culture, microbiological profile, along-with identification and antibiotic susceptibility by VITEK 2. PCT and CRP values were also compared. The outcome was then evaluated. Data analysis was done using SPSS V-20. Results: A total of 55 patients out of 140 patients, tested positive for Mucormycosis, either by KOH, culture or both. Rhizopus arrhizus was the most common isolate identified. A total of 12/55 (21.8%) people with Mucormycosis developed secondary infections during their stay in the hospital, bloodstream infection being the most common (7/15; 46.67%). Overall, gram-negative (GN) organisms were more common (11/16; 68.75%), in comparison to Gram Positives (GP) (5/16; 31.25%), but the most common organism isolated was Enterococcus faecium (5/16; 31.25%), followed by Klebsiella pneumoniae (4/16) and E. coli (4/16). A total of 4/5 isolates (80%) of Enterococcus faecium were multi-drug resistant (MDR) and two of them were vancomycin-resistant. In all, 10/11 GN isolates (90.9%) were MDR, high resistance to carbapenems was observed, nine out of 11(81.81%) isolates were resistant to imipenem and eight (72.72%) were resistant to meropenem. A total of 3/12 (25%) patients succumbed to their infection in the group with secondary infections, after an average length of stay of 23.33 days. The most common cause of death in these patients was septic shock. A total of 8/43 (18.6%) succumbed to their infection in the group without any secondary infection at an average stay of 9.12 days in the hospital. CRP was found to be consistently elevated, this biomarker might not have a predictive value for bacterial infections in COVID-19 but PCT had a positive predictive value for the secondary bacterial infections overall ( P -value <.001). Length of stay in hospital co-related with the development of secondary infection and mortality ( P -value <.001). Conclusion: Culture-based testing should be carried out before the administration of anti-microbials. PCT can be used as a guiding tool. Controlled use of antibiotics along with periodic surveillance and hand hygiene practices will immensely contribute to infection control.